PENGARUH IKLIM SEKOLAH TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP ISLAM ASHABUL KAHFI PONTIANAK - Irma Vidiyani; Asrori Asrori; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractSchool climate influences the way we do things at school. For example, in obtaining good learning outcomes in class VIII Islamic Middle School Ashabul Kahfi Pontianak. In the school climate there are also teacher behaviors and student behavior, teacher behavior and student behavior affect student learning outcomes. If the teacher's behavior and student's behavior is not good it will affect student learning outcomes that are not good, and vice versa. Because student learning success is determined based on student participation in schools such as work on assignments from the teacher, and participation in examinations. The general problem in this study is "How does the influence of the school climate on student learning outcomes in VIII grade Islamic Middle School Ashabul Kahfi Pontianak". the sub-problems are (1) What is the school climate at the Pontianak Ashabul Kahfi Islamic Middle School ?. (2) What are the learning outcomes of Grade VIII Middle School students at Ashabul Kahfi Pontianak? (3) Is there an influence of the school climate on the learning outcomes of students of class VIII SMPI Ashabul Kahfi Pontianak ?.The method used is descriptive method and the form of research is the study of influence. The population in this study were 73 students of class VIII Islamic Middle School Ashabul Kahfi Pontianak. Data collection techniques in this study are indirect communication and data collection tools used are questionnaires, while data analysis techniques use the percentage formula and product moment correlation.Keywords : school climate, learning outcomesAbstractSchool climate influences the way we do things at school. For example, in obtaining good learning outcomes in class VIII Islamic Middle School Ashabul Kahfi Pontianak. In the school climate there are also teacher behaviors and student behavior, teacher behavior and student behavior affect student learning outcomes. If the teacher's behavior and student's behavior is not good it will affect student learning outcomes that are not good, and vice versa. Because student learning success is determined based on student participation in schools such as work on assignments from the teacher, and participation in examinations. The general problem in this study is "How does the influence of the school climate on student learning outcomes in VIII grade Islamic Middle School Ashabul Kahfi Pontianak". the sub-problems are (1) What is the school climate at the Pontianak Ashabul Kahfi Islamic Middle School ?. (2) What are the learning outcomes of Grade VIII Middle School students at Ashabul Kahfi Pontianak? (3) Is there an influence of the school climate on the learning outcomes of students of class VIII SMPI Ashabul Kahfi Pontianak ?.The method used is descriptive method and the form of research is the study of influence. The population in this study were 73 students of class VIII Islamic Middle School Ashabul Kahfi Pontianak. Data collection techniques in this study are indirect communication and data collection tools used are questionnaires, while data analysis techniques use the percentage formula and product moment correlation. Keywords : school climate, learning outcomes